Simulation of Prototype Active Agricultural Solar Dryer with Slit-Type Transpired Solar Collector - Kuhe, A.; Ibrahim, J. S.; Tuluen, L. T.; Akanji, S. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper presents a functional and easy method for simulation of thin bed drying of maize in an active solar dryer with slit-type transpired collector using TRNSYS software. Thin layer solar drying model written in TRNSYS equation blocks in combination with existing components in the software library were used to build a solar mixed mode dryer system in TRNSYS environment for simulation. Experimental data for thin-bed solar dryer drying of maize obtained at different air mass flow rates of 0.026, 0.033, 0.034, 0.035 and 0.038 kg/sec, respectively, were used for model verification. There was good agreement between simulation results and experimental dryer temperatures for thin-bed solar dryer drying of maize with root mean square error (RMSE) and Nash- Sutcliffe efficiency coefficient (NSE) of 0.95, 0.57, 0.65, 1.15, 1.32 and 0.92, 0.93, 0.92, 0.85, 0.89 respectively for the air mass flowrates investigated. The results further confirmed that TRNSYS software can be a useful tool in the design and optimization of solar dryer systems.